2015
DOI: 10.1016/j.jmbbm.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Wear and biological effects of a semi-constrained total disc replacement subject to modified ISO standard test conditions

Abstract: Total disc replacement wear and the potential for osteolysis is a growing concern, therefore a parametric study on the effects on wear of altered kinematics and loading was undertaken. A standard ISO testing protocol was modified in order to study the wear behaviour of lumbar total disc replacements when subject to low cross shear input kinematics, reduced axial loading and smaller flexion-extension magnitude. Volumetric wear, bearing surface topography, and wear debris biological reactivity were assessed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…The average wear from this experiment and those described above is approximately six times lower than the average of L-TDR wear results reported for multi-path motions similar to the ISO inputs. 17,19,[22][23][24][25][26] The increase in wear under higher protein lubricant concentration has been observed in MoP hip replacement tests by Wang et al, 27 but conversely, Liao et al 28 have reported the opposite trend. The accidental damage (and subsequent exclusion) of three of the test discs for the final two simulator studies demonstrated that the UHMWPE discs are susceptible to damage when off-centre positioning of the metallic cup is combined with loading.…”
Section: Discussionmentioning
confidence: 99%
“…The average wear from this experiment and those described above is approximately six times lower than the average of L-TDR wear results reported for multi-path motions similar to the ISO inputs. 17,19,[22][23][24][25][26] The increase in wear under higher protein lubricant concentration has been observed in MoP hip replacement tests by Wang et al, 27 but conversely, Liao et al 28 have reported the opposite trend. The accidental damage (and subsequent exclusion) of three of the test discs for the final two simulator studies demonstrated that the UHMWPE discs are susceptible to damage when off-centre positioning of the metallic cup is combined with loading.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the zero CS plates had a dull appearance compared to the burnished wear tracks 278 observed on the plates subject to CS. This could be due to work-hardened wear particles acting 279 as third body wear debris 37 . 280…”
Section: Discussion 210mentioning
confidence: 99%
“…A recently published conference article on TDR wear debris reported a similarity to hip and knee particle morphology and is therefore a long‐term concern. Further work on biological reactivity of in vitro gathered lumbar TDR wear debris has been reported separately …”
Section: Discussionmentioning
confidence: 99%
“…Further work on biological reactivity of in vitro gathered lumbar TDR wear debris has been reported separately. 44…”
Section: Discussionmentioning
confidence: 99%